Peningkatan Hasil Belajar Matematika Melalui Metode Pembelajaran Kooperatif Model STAD (Student Teams Achievement Division) Pada Siswa Kelas X SMA Darul Ulum Tapen - Duwi Wahyuning Tias (Pedir Research Institute, 2021)
Learning Mathematics no longer prioritizes absorption through the attainment of information, but rather focuses on developing abilities and processing information. For this reason, student activity needs to be increased through math exercises or assignments by working in small groups and explaining ideas to others. Cooperative learning model The STAD (Student Teams Achievement Division) model is one of the most appropriate models used in implementing learning achievement. The benefits of this research 1. Can be used by schools in an effort to improve the quality of student learning outcomes, especially at Darul Ulum Tapen High School, 2. As one of the considerations for teachers in determining learning models and methods, especially mathematics, and 3. Knowing the results of student achievement using cooperative models and STAD method. The results of this study cooperative learning with the STAD model have a positive impact on improving student learning outcomes which are marked by an increase in student learning completeness in each cycle, namely cycle I (65.22%), cycle II (78.26%), cycle III ( 86.96%).